2017
DOI: 10.4103/0019-5413.197554
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of anatomic locking plate in extraarticular distal humeral shaft fractures

Abstract: Background:Extraarticular fractures of distal humerus are challenging injuries to treat because of complex anatomy and fracture patterns. Functional bracing may not provide adequate stability in these injuries and operative treatment with intramedullary nails or conventional plates also has the limitation of inadequate fixation in the short distal fragment. The 3.5 mm precontoured single column locking plate (extraarticular distal humerus plate [EADHP]) has been introduced to overcome this problem. We evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
(48 reference statements)
0
23
0
1
Order By: Relevance
“…16,17 Other plate designs like the Lambda plate and metaphyseal locking plate have also been described, but none of them are as efficient as the EADHP in terms of biomechanical stability and lesser complications. [18][19][20] In our study, 30 patients were males indicating the higher incidence of distal humerus fractures in males than in females. Most of the fractures occurred due to high energy trauma i.e.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…16,17 Other plate designs like the Lambda plate and metaphyseal locking plate have also been described, but none of them are as efficient as the EADHP in terms of biomechanical stability and lesser complications. [18][19][20] In our study, 30 patients were males indicating the higher incidence of distal humerus fractures in males than in females. Most of the fractures occurred due to high energy trauma i.e.…”
Section: Discussionmentioning
confidence: 50%
“…The authors concluded that EADHP is a reliable option for treatment of these fractures with stable fixation which gives early return to function. 20 There are numerous other studies which document the efficiency of this plate in treatment of distal humerus fractures. 17,22 The limitations of our study are small sample size and lack of a control group to compare the results.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our series, 60% EADHF were wedge or complex type. Kharbanda Y et al and Jain D et al respectively had 75% and 84.6% of patients in their series having a wedge fragment or complex type of fracture pattern [ 4 , 21 ]. Incidence of distal humeral fractures is on rise due to high velocity road traffic accidents and the elderly women with osteoporosis is the most vulnerable group [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scolaro described the use of a pre-contoured distal humerus locking plate for distal humerus extraarticular fractures ( Figure 5D) [11]. Also, Jain et al used an extra articula posterolateral locking plate and reported a reoperation rate of 15.4% [3].…”
Section: Research Articlementioning
confidence: 99%
“…Optimal treatment of these injuries is surgical, providing a predictable alignment quicker return to pre injury status [2] Stable fixation and reduced surgical time lead to fewer complications and allow earlier rehabilitation leading to a more predictable result. In the the clinical and functional outcomes using the extraarticular distal humerus plate in the management of extraarticular fractures of distal humerus were studied [3]. Anatomy of distal humerus is complex, and often the fracture pattern adds o the complexity of situation [4].…”
Section: Introductionmentioning
confidence: 99%